Agency and the Pedagogy of Japanese Colonialism in Tan Twan Eng's The Gift of Rain - Lim, David C. L. (2011)
What is the location of agency? And to what extent do historical contingencies and other causalities set the limits of self-autonomy, particularly during the time of Japanese colonialism? This article critically examines how these questions are explored in Tan Twan Eng's novel, The Gift of Rain, essentially the protagonist's autonarrative. Reading the text beyond its popular and authorial representation, and teasing out its homoerotic kernel, I make a case against the protagonist's romantic displacement of agency to the transcendental heart, arguing that Philip Hutton, the protagonist, is in the final account not only far more unfree than he believes, he is also much freer than he knows. [ABSTRACT FROM AUTHOR].